1967. Receipt of Influenza Vaccination as Predictor of COVID-19 Vaccination among United States Veterans. (15th December 2022) - Oda, Gina; Sharma, Aditya; Lucero-Obusan, Cynthia A; Schirmer, Patricia; Holodniy, Mark
Abstract: Background: Vaccine hesitancy has been a major barrier during the COVID-19 pandemic. Surveys administered to assess vaccine acceptance have indicated several factors associated with individual's intention to receive COVID-19 vaccination, including risk perception, concern for side effects, political orientation, male sex, and having received an influenza (flu) vaccine. However, it is unknown whether these factors predict receipt of vaccination. We sought to determine factors that predicted COVID-19 vaccination in the Veterans Health Administration (VHA). Methods: We extracted COVID-19 vaccine status among Veterans with any VHA outpatient or inpatient visit from 12/01/2020 - 12/01/2021 from the VHA Corporate Data Warehouse. To ensure participants were engaged in ongoing VHA care, deceased individuals, and those with no visits in the prior year were excluded. We estimated association of proportion of years of VHA care in which influenza vaccine was received in the preceding 5 years with COVID-19 vaccination by logistic regression, adjusting for age, sex, and rurality of home address. Results: We identified 5, 700, 590 Veterans with outpatient/inpatient visits during the study period, with median age 66 years, of whom 5, 131, 617 (90%) were male. A total of 3, 704, 617 (65%) received at least 1 COVID-19 vaccination. Individuals who received influenza vaccination during each year in care had more than 4 times the odds of receiving COVID-19 vaccination than those who never received influenza vaccination. (Table 1). Age groups 50-64 years had twice the odds, and years 65-74 and over 75 had 3 times the odds of receiving COVID-19 vaccination versus those 18-49, while Veterans living in rural and highly rural areas had lower odds of receiving COVID-19 vaccination versus those in urban areas. Table 1. Multiple logistic regression analysis of predictors of COVID-19 vaccination among Veterans cared for in the Veterans Health Administration, December 2020 – December 2021. N=5, 700, 590 Abbreviations: aOR = Adjusted Odds Ratio, CI = Confidence Interval. 1 Proportion of years in care influenza vaccine received was calculated by dividing the total number of years a Veteran received influenza vaccine by the total number years the Veteran received care for the 5 years prior to the study time period. 2 VHA uses the Rural Urban Commuting Areas (RUCA) system to define rurality (RURAL VETERANS - Office of Rural Health (va.gov) Conclusion: Influenza vaccination on a regular basis (i.e., annually) was strongly linked to receipt of COVID-19 vaccination, indicating that prior influenza vaccine acceptance predicted COVID-19 vaccination. Public health efforts to reduce vaccine hesitancy (including targeted messaging to younger individuals, and those in rural areas) are important to increase vaccine acceptance in preparation for the next pandemic, as well as to decrease annual disease burden. Disclosures: All Authors : No reported disclosures.